Presumptive antibiotics in tube thoracostomy for traumatic hemopneumothorax: a prospective, Multicenter American Association for the Surgery of Trauma Study. Issue 1 (4th November 2019) - Cook, Alan; Hu, Chengcheng; Ward, Jeanette; Schultz, Susan; Moore III, Forrest O'Dell; Funk, Geoffrey; Juern, Jeremy; Turay, David; Ahmad, Salman; Pieri, Paola; Allen, Steven; Berne, John
Abstract : Background: Thoracic injuries are common in trauma. Approximately one-third will develop a pneumothorax, hemothorax, or hemopneumothorax (HPTX), usually with concomitant rib fractures. Tube thoracostomy (TT) is the standard of care for these conditions, though TTs expose the patient to the risk of infectious complications. The controversy regarding antibiotic prophylaxis at the time of TT placement remains unresolved. This multicenter study sought to reconcile divergent evidence regarding the effectiveness of antibiotics given as prophylaxis with TT placement. Methods: The primary outcome measures of in-hospital empyema and pneumonia were evaluated in this prospective, observational, and American Association for the Surgery of Trauma multicenter study. Patients were grouped according to treatment status (ABX and NoABX). A 1:1 nearest neighbor method matched the ABX patients with NoABX controls. Multilevel models with random effects for matched pairs and trauma centers were fit for binary and count outcomes using logistic and negative binomial regression models, respectively. Results: TTs for HPTX were placed in 1887 patients among 23 trauma centers. The ABX and NoABX groups accounted for 14% and 86% of the patients, respectively. Cefazolin was the most frequent of 14 antibiotics prescribed. No difference in the incidence of pneumonia and empyema was observed between groups (2.2% vs 1.5%, p=0.75). Antibiotic treatment demonstrated a positive but non-significant association with risk of pneumonia (OR 1.61; 95% CI: 0.86 3.03; p=0.14) or empyema (OR 1.51; 95% CI: 0.42 5.42; p=0.53). Conclusion: There is no evidence to support the routine use of presumptive antibiotics for post-traumatic TT to decrease the incidence of pneumonia or empyema. More investigation is necessary to balance optimal patient outcomes and antibiotic stewardship. Level of evidence: II Prospective comparative study